2021
DOI: 10.1002/htj.22191
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Darcy–Forchheimer drag coefficients and velocity slip on the flow of micropolar nanofluid

Abstract: The flow of magneto-micropolar nanofluid, that is, the composition of TiO 2 nanoparticles in an organic solvent, kerosene, and the normal water past a stretchable surface has been considered. With effectiveness idea on the application in several areas, the Darcy-Forchheimer inertial drag and the second-order velocity slip approach are vital for the current investigation. The influence of viscous, Joule and Darcy dissipations on the energy transfer cannot be neglected due to the interaction of the body forces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The computation is iterated until some kind of convergence criterion is met up to the desired level of accuracy of 10 5, at which point it stops. Hassanien et al, 48 Salleh and Nazar 49 and Fadzilah et al 50 already had results that were very similar to what we found. Table 1 shows that there is a great fit.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The computation is iterated until some kind of convergence criterion is met up to the desired level of accuracy of 10 5, at which point it stops. Hassanien et al, 48 Salleh and Nazar 49 and Fadzilah et al 50 already had results that were very similar to what we found. Table 1 shows that there is a great fit.…”
Section: Resultssupporting
confidence: 91%
“…In view of the above research title, other recent and relevant published work can be found in. 4752…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In aircraft, the continuous feeding and discharging of the fluid can minimize catalyst deactivation. In addition, characterized by high thermal conductivity, nanofluids can be used as a new material to replace the EHFs. …”
Section: Introductionmentioning
confidence: 99%
“…Heat and velocity transfer rate has been analysed by in the scenarios of Changes in the parameters of nanofluid heat transfer as a result of the interaction between an incline magnetic field and an uneven heat source Effect of velocity slip on a micropolar fluid's MHD flow across a stretching surface. A computational approach to the dynamics of dust particles in a conducting water-based kerosene nanomaterial examining the effects of metallic nanoparticles on magnetohydrodynamics: Cu, Al 2 O 3 , and SWCNTs Water-based nanofluid via a porous medium features of velocity slip and Darcy-Forchheimer drag coefficients in micropolar nanofluid flow combinatorial chemistry and high throughput screening: Free Convective flow of Hamilton-crosser model Gold-water Nanofluid through a channel with permeable moving walls investigation has been done by the researchers [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%